Парламентські вибори 2007 та 2012 років в Україні: електоральні тренди та виклики - Малиновський, Валентин Ярославович; Malynovskyi, Valentyn YA. (Рівненський державний гуманітарний університет, 2013)
У статті розглянуто результати виборів до Верховної Ради України 2007 і 2012 років. На основі компаративного аналізу результатів двох виборчих кампаній зроблено висновки щодо електоральних трендів на вітчизняній політичні арені.

The article deals with the results of the parliamentary elections in Ukraine in 2007 and 2012, the conclusions about electoral trends in the domestic political arena based on comparative analysis of two election campaigns. The winner of the two campaigns was the Party of Regions. However, there is a trend that this party is losing supporters in the East – in the regions of the largest support and an increase in the West and Central Ukraine. However, despite this, it again won the elections, because the united opposition could not defeat it that has given the status of the ruling party which can not be defeated. The last parliamentary elections showed the request of Ukrainian society in the radical direction idea. Significant growth of supporters of the Communist Party and the first ever Ukrainian parliamentary passage to the Verkhovna Rada nationalist party «Svoboda» confirms this thesis. These two ideological parties showed that actual voter ideas can overcome financial and technological projects. Quite convincing passage to the Verkhovna Rada V. Klitschko’s Party «UDAR» (third place) confirms another national electoral trend – the request in new faces and political projects. V. Klitschko largely echoed the S. Tihipko’s way who confidently broke into a higher echelon of Ukrainian politics during the last presidential election. Saved a difference between types of political culture in the regional dimension, however, reduce disparities in the results and will shift to the new political constituency projects show a decrease (albeit small) regional polarization. With the growth of the election’s technological successful debut V. Klitschko and failure of the N. Korolevska’s project shows that charismatic electoral culture dominates technological approach and the thesis «the one who better enforces information is winner» does not always work. Primary importance to voters played the following characteristics of party: ideological framework and electoral program, the person of the party leader, a positive attitude towards previous activities of the party.
Parliamentary elections 2007 and 2012 in Ukraine: electoral trends and challenges
Keywords: парламентські вибори; parliamentary elections; Верховна Рада України; Verkhovna Rada of Ukraine; виборча система; the electoral system; партія; the party; опозиція; the opposition; електорат; the electorate; народний депутат України; MP of Ukraine